2007
DOI: 10.1007/s10735-007-9148-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of TGF-β1 on the expression of BSP, DSP, TGF-β1 receptor I and Smad proteins during reparative dentinogenesis

Abstract: Reparative dentin has a wide variety of manifestations ranging from a regular, tubular form to an irregular, atubular form. However, the characteristics of reparative dentin have not been clarified. This study hypothesized that the level of bone sialoprotein (BSP) expression will increase if the newly formed reparative dentin is bone-like but the dentin sialophosphoprotein (DSPP) level will decrease. In order to test this hypothesis, the expression of BSP and DSP was examined by immunohistochemistry and the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 27 publications
2
57
0
4
Order By: Relevance
“…Regarding the regenerative process after tooth injuries such as cavity preparation and pulpal capping following pulp exposure, newly differentiated or surviving odontoblast-like cells express Dsp protein in addition to the immunoreaction in the tertiary dentin (14,25), suggesting that this protein is a reliable marker for regenerated odontoblasts and tertiary dentin. However, immunohistochemistry for Dsp is unable to determine the up-regulation of Dsp production in the afflicted odontoblasts, because Dsp protein has already been accumulated in their cytoplasm.…”
Section: Molar At Week 3 (Table 2)mentioning
confidence: 99%
“…Regarding the regenerative process after tooth injuries such as cavity preparation and pulpal capping following pulp exposure, newly differentiated or surviving odontoblast-like cells express Dsp protein in addition to the immunoreaction in the tertiary dentin (14,25), suggesting that this protein is a reliable marker for regenerated odontoblasts and tertiary dentin. However, immunohistochemistry for Dsp is unable to determine the up-regulation of Dsp production in the afflicted odontoblasts, because Dsp protein has already been accumulated in their cytoplasm.…”
Section: Molar At Week 3 (Table 2)mentioning
confidence: 99%
“…Dental pulp cells can contribute to this process, and dentin ECM proteins actively promote and control mineralization of collagen fibers and apatite crystal growth during conversion of predentin to dentin (Butler et al, 2003). One ECM protein of notable importance is dentin sialophosphoprotein (DSPP), which undergoes cleavage to DPP (dentin phosphoprotein) and DSP (dentin sialoprotein), is associated with dentin mineralization (Papagerakis et al, 2002), and is expressed by odontoblast-like cells underlying newly formed reparative dentin Hwang et al, 2008).…”
Section: Introduction Dmentioning
confidence: 99%
“…It has been found that BSP binding to HA and collagen may promote bone mineralization [Hunter and Goldberg, 1993;Baht et al, 2008]. While BSP has been identified in porcine, rat and human dentin, its role in dentin mineralization is still unknown [Chen et al, 1993;Boukpessi et al, 2008;Huang et al, 2008;Hwang et al, 2008].…”
mentioning
confidence: 99%